1997
DOI: 10.1111/j.1432-1033.1997.0482a.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Minor and Major Groove‐Binding Drugs and Intercalators on the DNA Association of Minor Groove‐Binding Proteins RecA and Deoxyribonuclease I Detected by Flow Linear Dichroism

Abstract: Linear and circular dichroic spectroscopies have been employed to investigate the effects of small DNA ligands on the interactions of two proteins which bind to the minor groove of DNA, viz. RecA protein from Escherichia coli and deoxyribonuclease 1 (bovine pancreas). Ligands representing three specific non-covalent binding modes were investigated: 4',6-diamidino-2-phenylindole and distamycin A (minor groove binders), methyl green (major groove binder), and methylene blue, ethidium bromide and ethidium dimer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…Our results clearly indicated that SC-dots could influence the interactions between DNA and MG, a proven DNA major groove binder (29,45,46). Figure 4B showed CD spectral changes in the presence of SC-dots.…”
Section: Resultsmentioning
confidence: 51%
“…Our results clearly indicated that SC-dots could influence the interactions between DNA and MG, a proven DNA major groove binder (29,45,46). Figure 4B showed CD spectral changes in the presence of SC-dots.…”
Section: Resultsmentioning
confidence: 51%
“…The further digestion and subsequent shortening of the DNA resulted in a decrease in the magnitude of the LD (20). A decrease in the magnitude of the LD reflecting the shortening of the DNA due to double strand cleavage by deoxyribonuclease I has also been reported (22). In this case, the decrease in the magnitude of the LD was able to be modeled as a single exponential decay.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, methyl green, a DNA major groove binder [25], [26] was used as a major groove binding competitor for this competitive experiment. As shown in Figure 6A, in the presence of methyl green, no distinct effect on DNA band shifting could be observed on the agarose gel.…”
Section: Resultsmentioning
confidence: 99%